System Manajemen Kinerja Pada Usaha Tani Padi Menggunakan Pendekatan KBPMS: Sebuah Kerangka Konseptual - Rhanni Apriani Wirdhawan; Dermawan Wibisono (AGRIMOR, 2023)
In general, food security is the most important thing in a country, one of which is Indonesia. Indonesia itself has land or land that can be used to produce food including rice, corn, fruits and grains. Thus, enabling Indonesia to be immune to food availability. However, on the other hand, farmers who are the driving force in food production have a low level of welfare. There are several possibilities why the welfare of farmers is still low, the capital spent is greater than their income. For personal consumption, farmers decide not to sell some of their crops. so that the profit is not maximized. There are also farmers who experience crop failure due to pest attacks. Excessive use of seeds or fertilizers can affect crop yields. Thus, a performance management system is needed for rice farming to be able to control, monitor, and evaluate. This is intended so that farming becomes effective and efficient. This study aims to build a framework for the performance management of rice farming using a knowledge-based Performance management system approach. A qualitative approach was used in this study and data were collected from 50 journal articles taken at Google Scholar. The results of this study found 21 performance variables, namely 3 of them on the aspect of resource capability, 12 of them on the aspect of internal processes and 6 of them on aspects of organizational output and the framework of interrelationships between performance variables.